A segmentation of Turkish consumers based on their motives to visit shopping centres. Issue 4 (7th August 2016) - Kabadayi, Sertan; Paksoy, Banu
Abstract: This paper aims to contribute to the literature by providing a segmentation of Turkish consumers based on their motives for visiting shopping centres. First, we identified the motives that Turkish consumers had for visiting shopping centres and then we used those motives to segment consumers. Data were collected through a survey from 390 participants living in the six largest cities in Turkey. First, the results showed that Turkish consumers had five groups of motives when it comes to visiting shopping centres. The results of a two-step cluster analysis used for segmentation revealed four distinct segments of Turkish shopping centre visitors. Those segments were named as serious consumers, recreational consumers, enthusiast consumers, pragmatic consumers. These findings suggest that Turkish shopping centre managers need to recognize that Turkish consumers are not a homogeneous unit when it comes to visiting shopping centres. Finally, academic and managerial implications of our findings are discussed.